N-Acetylcysteine and Sulodexide Reduce the Prothrombotic Effect of Uremic Serum on the Venous Endothelial Cells - Patrycja Sosinska-Zawierucha; Beata Mackowiak; Andrzej Breborowicz (Karger Publishers, 2019)
Background/Aims: Thromboembolic episodes are a frequent problem in end stage renal failure patients. The pathomechanism of the disorder is complex, including bioincompatibility of renal replacement therapy, endothelial dysfunction, increased blood level of procoagulant factors and uremic toxins. We studied changes in the functional properties of venous endothelial cells (VEC) in the presence of uremic serum and evaluated their possible modulation by N-acetylcysteine (NAC) or sulodexide (SUL). Methods: Serum samples from 12 uremic patients treated with hemodialysis were studied ex vivo on in vitro cultured VEC. In separate experiments, NAC 1 mmol/L or SUL 0.5 LRU/mL were added to uremic serum samples. Both changes in the gene expression and secretory activity of VEC were studied. Results: Uremic serum increased the expression of the following genes: IL6 +97%, p < 0.002; VEGF +28%, p < 0.002; vWF +47%, p < 0.002; PECAM +76%, p < 0.002; ICAM-1 +275%, p < 0.002; t-PA +96%, p < 0.002. Changes in gene expression were reflected by the increased secretory activity of VEC treated with the uremic serum. Exposure of VEC to uremic serum supplemented with NAC or SUL resulted in weaker stimulation of the studied genes' expression. Also, secretion of the studied solutes, with the exception of ICAM-1, was reduced in the presence of NAC: IL6 -34%, p < 0.01; VEGF -40%, p < 0.005; vWF -25%, p < 0.001; t-PA -47%, p < 0.01, and MMP9 -37%, p < 0.001. SUL reduced the uremic serum-induced secretion of all solutes: IL6 -24%, p < 0.05; ICAM-1 -43%, p < 0.01; VEGF -38%, p < 0.01; vWF -23%, p < 0.01; t-PA -49%, p < 0.01, and MMP9 -25%, p < 0.05. Conclusions: Uremic serum induces prothrombotic changes in VEC, which may cause a predisposition to thrombotic disorders in patients with renal failure. NAC and SUL reduce the effects of the uremic serum in VEC, which suggests their potential therapeutic application in uremic patients.